2016
DOI: 10.4238/gmr.15027890
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species amplification and polymorphism of microsatellite loci in Helicoverpa armigera and Helicoverpa zea (Lepidoptera: Noctuidae) in Brazilian cropping systems

Abstract: ABSTRACT. The Old World bollworm Helicoverpa armigera (Hübner) was recently discovered in Brazil. This species is closely related to the New World bollworm H. zea (Boddie), and mating between these species has already been reported under laboratory conditions. Here, we tested the cross-species amplification of 20 microsatellite (SSR) loci in field populations of H. armigera and H. zea collected from Brazilian cropping systems. Seven SSR loci were successfully amplified and polymorphic in both species except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Microsatellite DNA markers in the Lepidoptera including Helicoverpa species are often affected by transposable elements (Gordon, Tay, Collinge, Williams, & Batterham, ; Tay, Behere, Batterham, & Heckel, ), and alternative nuclear DNA markers should be used instead where possible (i.e., EPIC‐PCR markers, see Behere, Tay, Russell, Kranthi, and Batterham () and Tay, Behere, Heckel, Lee, and Batterham (). Nevertheless, signatures of interspecific H. armigera ‐ H. zea hybridization as inferred from microsatellite loci have been reported by Leite et al (). Future monitoring of Helicoverpa species at preborder inspection could also consider the method of Nagoshi, Gilligan, and Brambila () that incorporates the z‐linked Triosephosphate isomerase (Tpi) gene with the mtCOI gene for identifying potential H. armigera ‐ H. zea hybrids, although the feasibility of transferring this method to screen for potential H. armigera ‐ H. gelotopoeon , H. assulta ‐ H. gelotopoeon , H. assulta ‐ H. zea , and H. armigera ‐ H. assulta hybrids remained to be tested.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Microsatellite DNA markers in the Lepidoptera including Helicoverpa species are often affected by transposable elements (Gordon, Tay, Collinge, Williams, & Batterham, ; Tay, Behere, Batterham, & Heckel, ), and alternative nuclear DNA markers should be used instead where possible (i.e., EPIC‐PCR markers, see Behere, Tay, Russell, Kranthi, and Batterham () and Tay, Behere, Heckel, Lee, and Batterham (). Nevertheless, signatures of interspecific H. armigera ‐ H. zea hybridization as inferred from microsatellite loci have been reported by Leite et al (). Future monitoring of Helicoverpa species at preborder inspection could also consider the method of Nagoshi, Gilligan, and Brambila () that incorporates the z‐linked Triosephosphate isomerase (Tpi) gene with the mtCOI gene for identifying potential H. armigera ‐ H. zea hybrids, although the feasibility of transferring this method to screen for potential H. armigera ‐ H. gelotopoeon , H. assulta ‐ H. gelotopoeon , H. assulta ‐ H. zea , and H. armigera ‐ H. assulta hybrids remained to be tested.…”
Section: Discussionmentioning
confidence: 95%
“…The restriction enzymes selected represented a more comprehensive in silico analysis of publicly available partial COI sequences and avoided the need to include the partial Cyt b gene RFLP analysis originally designed by Behere et al (). The revised RFLP method has not included the restriction enzymes identified by both Arneodo et al () and Behere et al () because of novel mtCOI haplotypes identified from global populations of H. armigera including from South America (e.g., Arnemann, ; Arnemann et al, ; Leite et al, ; Tay, Walsh et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high frequency of the chimeric P450 enzyme CYP337B3 gene in H. armigera populations indicates that pyrethroid insecticides should not be recommended in Brazil or in the rest of the Americas, due to the high dispersal capacity and gene flow among H. armigera populations (Feng et al, 2005;Jones et al, 2015;Leite et al, 2016).…”
Section: Discussionmentioning
confidence: 99%